Масштаби, спрямованість та наслідки інвазій чужорідних видів риб у дніпровські водосховища - Новіцький, Роман Олександрович; Novitsky, R. A.; Novitsky, R. O.; Novitskiy, R. A.; Novitskiy, R. O.; Novickii, R. A.; Novitskij, R. A.; Novitskij, R. O.; Nowicki, R. A.; Novickij, R. A.; Novitskyy, R. O.; Novitskyi, R. O.; et al. (My University, 2019)
Дисертаційна робота присвячена з’ясуванню наслідків інвазій для структури та функціонування іхтіоценозів дніпровських водосховищ, визначенню масштабів, спрямованості сучасного інвазійного процесу у водосховищних екосистемах України. Вперше проведена інвентаризація чужорідних видів риб у каскаді дніпровських водосховищ, з’ясовані зміни структури іхтіоценозів внаслідок впливу інвазій. Основною водоймою-донором для дніпровських водосховищ є Чорне море, водночас водосховища каскаду виступають донорами понто-каспійської фауни для р. Прип’ять і Верхнього Дніпра, та для басейну р. Сіверський Донець через канал «Дніпро-Донбас». Ключовими моментами у розповсюдженні понто-каспійських видів у басейні Дніпра стали будівництво водосховищ і системи каналів, «лімнізація» ріки та глобальні заходи з акліматизації кормової для риб понто-каспійської фауни у водосховища. Успіх інвазій чужорідних видів обумовлений також змінами структури іхтіофауни під впливом антропогенних чинників. Знайдено, що у дуже трансформованих та деструктивних екосистемах значення зоофагів зростає, що пояснюється утворенням значної біомаси зообентосу. Доведено, що чужорідний вид Lepomis gibbosus має два вектори розповсюдження по каскаду: з пониззя Дніпра – у Каховське водосховище і з Дніпровського – у Кам’янське. Філогеографічний аналіз популяцій цього виду з Дніпра, Дністра і Дунаю на основі аналізу мінливості локуса cyt b мтДНК засвідчив, що Lepomis gibbosus із Дніпровського водосховища походить з водойм басейну верхів’я р. Потомак, США (р ≥0,99). Вперше проаналізовані взаємовідносини аборигенних видів риб з видами-інвайдерами. Доведено, що для чужорідних видів властивий агресивний характер освоєння нових стацій, значна трофічна та біотопічна конкуренція з нативними видами. Визначено, що найбільший інвазійний потенціал у басейні Дніпра мають 4 чужорідні види риб: Carassius auratus gibelio, Pseudorasbora parva, Lepomis gibbosus і Perccottus glenii, які формують так званий «Чорний» список видів (Black List) у дніпровських водосховищах. Розроблена система моніторингу інвазійного процесу у водоймах України, яка включає аналіз інвазійного процесу, оцінку стану угруповань та популяцій чужорідних видів, з’ясування наслідків екосистемних змін, оцінку екологічних ризиків, прогнозування нових інвазій, прийняття управлінських рішень щодо охорони та раціонального використання водних біоресурсів. The dissertation is devoted to the study of the ichthyocenosis structure of the Dnieper reservoirs and their subordinate system that change under influence of alien fish species invasions. We determinate the scale, direction and consequences of the modern invasive process in the reservoir ecosystems of Ukraine. Novelty of this research consists in the next - for the first time an inventory of alien fish species has been carried out in the cascade of the Dnieper reservoirs and the structure of the ichthyocenoses these reservoirs as a result of invasions has been determined. Today, 24 types of invaderfish and settled by oneself are naturalized in the Dnieper basin from 36 alien fish being there. It is proved that the invasion, naturalization and distribution of alien species in the Dnieper reservoirs are an overall ecological process. The main water basin delivering alien fish for the Dnieper reservoirs is the Black Sea, and so we call it fish donor. The reservoirs of the cascade in turn act as donors of the Ponto-Caspian fauna for the river Pripyat and the Upper Dnieper (Kyivske Reservoir), for the basin of the river Siverskiy Donets (Kamyanske Reservoir and the Dnepr-Donbass Canal). It is proved that the Dnepr-Donbass channel is a transit water way for the promotion of alien species from the Dnipro Basin to the basins of Seversky Donets and Don. The construction of reservoirs and canal systems, the "limnization" of the river due to its transformation into a cascade of reservoirs and also global actions to acclimatize many species of Ponto-Caspian fauna fodder for fish in new for them reservoir conditions became the key moments in the distribution of Ponto-Caspian species in the Dnieper Basin. The success of invasions of alien species is also caused by changes in the functional structure of the ichthyofauna under the influence of anthropogenic factors. By the degree of transformation we distinguish the following aquatic ecosystems: medium-transformed, where there is a partially disrupted operation mode, but some features of the original system still exist; highly-transformed, where the river system is regulated, it has lost the properties of the outgoing habitats of biota with violation of biocenosis and population relationships, and destructive, where aquatic and terrestrial ecosystems are affected by direct influence of a number of factors, especially man-made (pollution, change of channels in the formation of quarries, etc.) and it is impossible to return to the initial state without the use of special works. In conditions created in the aquatic ecosystems of the Dnieper, relatively normal structural and functional indicators are maintained only in the medium-transformed ecosystems. The basis is zoophages (69.4%) with a marked role of predators (15.4%) and phytophages (11.7%). In highly-transformed ecosystems the value of zoophages increases by 1.2%, in destructive ones by 1.3 times. The value of phytophages and polyphages is reduced. The increase in the number of zoophages is due to the formation of a significant biomass of zoobenthos - especially oligochaetes, which development in contaminated areas remains. Reophylic groups in the medium-transformed systems are kept at a very low level - only 6.7%, while in small rivers with a little-transformed ecosystem - within 30-40%. In highly-transformed and destructive ecosystems they are completely absent. In such ecosystems only limnophilic groups remain. Anthropogenic transformation of small rivers of the Dnipro tributaries has led to a violation of the structure and integrity of ichthyocenoses. Fish groups are impoverished, trophofunctional structure is disturbed, monodominance of zoophages and absolute monodominance of limnophiles are increasing. The proportion of low-value and non-industrial species is increasing, and in the future they are completely dominant. Obviously, after a sharp destructive "jump" in technogenesis in the 1950-1960s, which led to simplification of the faunal and functional structure of ichthyotsenoses, the fish groups formed relatively stable adaptation. But the increase in technogenical impact on aquatic ecosystems in the 1980s and 1990s has undermined this weak adaptive stability. It has been detected that more than 50% of alien fish species in the Dnieper basin now have Ponto-Caspian origin, with a significant proportion of Asian species, and also alien fish species are being delivered from the Northern Europe region. An analysis of the species composition of fish-invaders indicates that the number of species is decreasing upstream. The process of self-resetting of species up the cascade of reservoirs of the Dnieper is the main vector of distribution of fish. In the lower part of the Dnieper, where the Pontic-Caspian fauna is aboriginal, the introduction of alien species is mainly associated with navigation, especially with the discharge of ballast waters. An important role in the Dnipro reservoirs belongs to periodic directed introduction of certain species. Since the late 1980s, fish invasion into the Dnieper basin has been characterized by explosive massive expansion, which occurs with acceleration. For the period from 2000 to 2007, the species composition of the Dnipro ichthyofauna has grown more than 2 times compared to the previous period of existence of the studied river. It is proved that the alien species of fish of the Dnieper reservoirs – Lepomis gibbosus has two vectors of distribution along the cascade: from the lower reach of the Dnieper to the Kakhovka reservoir and from the Dniprovske reservoir to the Kamyanske reservoir. Phylogeographic analysis of the populations of Lepomis gibbosus in the Dnieper, Dniester and Danube was conducted on the basis of the variability analysis of the cyt b mtDNA locus. It was determined with highly level of reliable (р ≥0,99) that L. gibbosus from the Dnieper reservoir is origin from the area of the secondary range of population - waters basin of the upper reaches of the river Potomac (USA). The example of alien species Pseudorasbora parva and Lepomis gibbosus shows the fish adaptation to habitats in the lotic and lentic ecosystems. It was shown that in the Kremenchugske and Dniprovske reservoirs fish with "lake-like" types of development are characterized by a higher body, which is necessary for the rapid release from the press of small predators. For the first time an analysis of the relationship between native fish species and species-invaders was carried out for the cascade of the Dnieper reservoirs. It has been proved that alien species have an aggressive character of adaptation to the new living conditions and more significant trophic and biotopic potential comparing with native species. The invasive strategies of alien species in the Dnipro reservoir have been investigated. The propagation velocity of Neogobius melanostomus, Syngnathus abaster, Lepomis gibbosus in the Dnipro reservoirs and their tributaries is calculated. It is shown that one of the consequences of the animal population transformation as a result of invasions is the fauna homogenization in reservoirs. The consequence of such homogenization may be the loss of ecosystem stability to any natural and anthropogenic impacts. Analysis of the dynamics of the change in the share of common species of fish in the ichthyofauna of Kakhovske and Dniprovske reservoirs showed that the similarity of ichthiofaunas of these reservoirs increased from 68% to 82% over the thirty years. The greatest invasive potential of the Dnieper Basin belongs to alien species Carassius auratus gibelio, Pseudorasbora parva, Lepomis gibbosus, Perccottus glenii. A system for monitoring the invasive process in Ukraine's water basins has been developed. It includes the analysis of the invasive process, assessment of the state of communities and populations of alien species, research of consequences ecosystem changes, assessment of environmental risks, prognosis of new invasions, creation of database for management of the aquatic biological resources protection and rational use. At the state level it is proposed to introduce National and regional programs for the prevention of the spread of invasive species.
Scale, direction and consequences of alien fish species invasions in the Dnieper reservoirs
Новіцький Роман Олександрович https://orcid.org/0000-0001-9373-5759
Keywords: водосховища; reservoirs; чужорідні види риб; alien fishes; інвазії; invasions; вектори інвазій; vectors of invasions; експансія; expansion; вселення; introduction; Дніпро; Dnieper